Heart rate variability in healthy term newborns is related to delivery mode: a prospective observational study - Marek Kozar; Ingrid Tonhajzerova; Michal Mestanik; Katarina Matasova; Mirko Zibolen; Andrea Calkovska; Kamil Javorka (BMC, 2018)
Abstract Background Early postnatal period is characterized by dramatic adaptation changes of cardiovascular and respiratory systems in newborns. There is still insufficient data regarding maturation of autonomic regulatory mechanisms in neonates early after delivery. Aim of this study was to analyze cardiac autonomic regulation in newborns within the first few postnatal days in relation to different modes of delivery using time and spectral heart rate variability analysis. Methods Eutrophic healthy term newborns (n = 46) were divided into three groups according to the delivery mode: vaginal delivery (VD group; n = 16), vaginal delivery with epidural analgesia (EDA group; n = 16), and caesarean section under general anesthesia (CS group; n = 14). Heart rate variability (HRV), blood pressure (BP), and blood oxygen saturation (SpO2) were measured within the first two hours after birth and on the third to fourth postnatal day. HRV parameters were evaluated in the time domain (RR intervals, mean square of successive differences - MSSD) and frequency domain (total spectral power - TP, absolute and relative low and high frequency powers). Results The HRV spectral analysis showed significantly higher relative power of the high-frequency band (HF%) in the VD group compared to the CS group early after delivery (p = 0.002). HRV parameters and BP significantly increased on the third to fourth postnatal day in all groups (p < 0.05). No significant differences in basic characteristics, BP and SpO2 were identified between groups during both measurements. Conclusions HRV analysis revealed higher cardiovagal modulation in spontaneously born newborns without analgesia compared to neonates born by caesarean section. It could represent a potential pathomechanism that leads to discrete abnormal neurocardiac regulation associated with higher risk for worsened postnatal adaptation of cardiovascular system in surgically delivered neonates.